Aqueous Extract of Unfermented Honeybush (Cyclopia maculata) Attenuates STZ-induced Diabetes and β-cell Cytotoxicity - Chellan, Nireshni; Joubert, Elizabeth; Strijdom, Hans; Roux, Candice; Louw, Johan; Muller, Christo J. F. (Planta Medica, 2014)
New strategies, which include β-cell protection, are required in the treatment of T2D, as current drugs demonstrate little or no capacity to directly protect the vulnerable β-cell against diabetes-induced cytotoxicity. In this study we investigated the ameliorative effect of pre-treatment with an aqueous extract of unfermented Cyclopia maculata (honeybush) on STZ-induced diabetes and pancreatic β-cell cytotoxicity in Wistar rats after demonstrating a protective effect in vitro in RIN-5F cells. The amelioration of STZ-induced diabetes was seen in the reduction of the area under the curve, determined by the oral glucose tolerance test, as well as fasting glucose levels in extract-treated rats. Pre-treatment with extract also improved serum triglyceride levels and the glucose-to-insulin ratio. Pre-treatment with the extract or the drug, metformin, increased the β-cell area in islets, with a concomitant increase in β-cell proliferation at the higher extract dose (300 mg/kg/d), but not the lower dose (30 mg/kg/d). Subsequently, the in vitro tritiated thymidine incorporation assay showed that the extract was not mitogenic in RIN-5F cells. STZ-induced elevation of plasma nitrite levels was reduced in extract-treated rats, but no changes were observed in their serum catalase, serum glutathione, liver lipid peroxidation and liver nitrotyrosine levels. Pre-treating the rats with extract ameliorated the diabetic effect of STZ in Wistar rats, with evidence of pancreatic β-cells protection, attributed to the presence of high levels of antioxidants such as the xanthones, mangiferin and isomangiferin.
Keywords: Cyclopia maculata; Fabaceae; mangiferin; diabetes; streptozotocin; β-cell; glucose tolerance